2008
DOI: 10.1111/j.1365-2036.2008.03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: treatment of hepatitis B infection reduces risk of hepatocellular carcinoma

Abstract: SUMMARY BackgroundChronic hepatitis B (CHB) infection leads to development of hepatocellular carcinoma (HCC), but the effects of treatment in preventing HCC are not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
260
4
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(279 citation statements)
references
References 41 publications
8
260
4
5
Order By: Relevance
“…11,19,20 A recent meta-analysis showed that the risk of hepatocellular carcinoma can be significantly decreased with viral suppression through antiviral therapy. 21 After NA withdrawal, relapse of viral infection can occur in most HBeAg-positive individuals that did not loose the HBeAg, as well as in HBeAg-negative individuals. The durability of drug induced viral suppression after a one-year treatment with lamivudine or adefovir in HBeAg patients has been < 10%.…”
Section: Viral Suppression Of Hbv-dnamentioning
confidence: 99%
“…11,19,20 A recent meta-analysis showed that the risk of hepatocellular carcinoma can be significantly decreased with viral suppression through antiviral therapy. 21 After NA withdrawal, relapse of viral infection can occur in most HBeAg-positive individuals that did not loose the HBeAg, as well as in HBeAg-negative individuals. The durability of drug induced viral suppression after a one-year treatment with lamivudine or adefovir in HBeAg patients has been < 10%.…”
Section: Viral Suppression Of Hbv-dnamentioning
confidence: 99%
“…As in HBV monoinfection, the long-term goal is to prevent cirrhosis and primary hepatoma by sustained suppression of viral replication to the lowest possible level [140].…”
Section: Goals Of Therapymentioning
confidence: 99%
“…2,3 Antiviral therapy is effective in suppressing HBV DNA and reducing the risk of hepatic events and HCC. 4,5 Lamivudine, the first generation oral nucleoside analogue was shown to reduce the incidence of hepatic events in patients with advanced fibrosis or compensated cirrhosis by 50%. 6 However, the clinical benefit may be negated by lamivudine resistance and virologic relapse after cessation of treatment.…”
mentioning
confidence: 99%